Salt-Tolerant Rhizobia for Enhancing Common Bean (Phaseolus vulgaris L.) Productivity under Salt Stress - Laurette, Ngo Nkot; Stephane, Youagang Gougueu Harris; Firmin, Semboung Lang; Laurence, Timb Sara Augustine; Lambert, Dongmo Kenfack Julio; Dieudonne, Nwaga (Review of Plant Studies, 2022)
Salinity is one of the most important abiotic factors which are responsible for lower yields. To reduce its impact, conventional methods have been unable to solve the problem at all. In this context, developing sustainable methods which increase the productivity of saline soils without harming the environment is necessary. Some microorganisms such as rhizobia are tolerant to salt stress and can then grow in saline areas. Therefore, salt tolerant (ST) rhizobia are believed to reduce the impact of salinity on plant productivity. The aim of this study is to select the major salt-tolerant isolate of rhizobia that can alleviate salt stress in the common bean. Five salt-tolerant rhizobia were used for bean inoculation in greenhouse under salt stress (0 mM, 25 mM and 50 mM). A month after sowing, plants are harvested and analyzed for nodulation, growth and biochemical stress markers production. Collected data are analyzed statistically using SPSS 12.0. Results show that plant inoculation with ISRA352, PvNk8, PvMb1, PvNk7 reduces the effects of stress through the increase of growth, total pigments and osmolytes (proline and glycine betaine) contents compared to positive and negative controls. Plant inoculation with PvMb1 and ISRA352 led to low stress at 50 mM of NaCl. PvMb1, PvNk8 and PvNj5 are good inoculants for bean cultivation even in salt-affected soils. This research study contributes to allow the cultivation of bean in salty areas. On the other hand, the study comes up with a solution for remediation of saline soils yet to be enhanced.